A randomized controlled trial of the web‐based drinking diary program for problem drinking in multi workplace settings. Issue 1 (13th January 2022) - Sunami, Takashi; So, Ryuhei; Ishii, Hironobu; Sadashima, Eiji; Ueno, Takefumi; Yuzuriha, Takefumi; Monji, Akira
Abstract: Objectives: To assess the effectiveness of a web‐based brief intervention (BI) program to record daily drinking among people with problem drinking in workplace settings. Methods: A two‐armed, parallel‐group, randomized controlled trial were conducted at six workplaces in Japan. After obtaining written consent to participate in the study, workers with an Alcohol Use Disorders Identification Test (AUDIT) score of 8 or higher were randomly assigned into two groups. The participants allocated to the intervention group recorded their daily alcohol consumption for 4 weeks using the program, while those allocated to the control group received no intervention. Outcome measures included the amount of alcohol consumption in past 7 days using the Timeline Follow‐Back method in the program at baseline, 8th week, and 12th week and written AUDIT score at baseline and 12th week. Results: Hundred participants were assigned to either the intervention group ( n  = 50) or control group ( n  = 50). The results of two‐way repeated measures ANOVA showed a statistically significant interaction between the group and the week factors in the two primary outcomes (number of alcohol‐free days, total drinks) and secondary outcomes (AUDIT score) ( p  = .04, .02, and .03, respectively). The between‐group effect sizes (Hedges' g ; 95% CI) of the outcomes at 12th week were 0.53; 0.13–0.93 (total drinks), 0.44; 0.04–0.84 (AUDIT score), 0.43; 0.03–0.83 (number of alcohol‐free days). Conclusions: The web‐based BI program for problem drinking was considered to be effective in reducing alcohol consumption and the AUDIT score in workplace settings.